(untitled) (Baghdad Science Journal, 2025)
Three complexes of copper(II) and iron(II) with mixed ligands acetylacetonebis(thio-semicarbazone)- ABTSH2 and benzaldazine- BA have been prepared and characterized using different physico-chemical techniques including the determination of metal contents, mole-cular weight, measurement of molar conductivity, magnetic moment, molar refraction, infrared and electronic spectra. Accordingly, octahedral complexes having general formulaes [Cu2(ABTSH2)2(BA)2Cl2]Cl2 and [M2(ABTSH2)2(BA)2(SO4)2] M= Cu(II) or (Fe(II) have been proposed. The resulted complexes screened for antifungal activity in vitro against the citrus pathogen Aspergillus niger and Fusarium sp. which caused root rot of sugar and the beans pathogen Alternaria sp. All the complexes exhibited significant antifungal activities against these pathogens. The antifungal activity of these complexes were comparable with the standard fungicides in ethanol. The complex [Cu2(ABTSH2)2(BA)2Cl2]Cl2 had the best antifungal activity against Alternaria sp.